2017
DOI: 10.1038/srep44434
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of arthritic bone degradation by analysis of 3D micro-computed tomography data

Abstract: The use of animal models of arthritis is a key component in the evaluation of therapeutic strategies against the human disease rheumatoid arthritis (RA). Here we present quantitative measurements of bone degradation characterised by the cortical bone profile using glucose-6-phosphate isomerase (G6PI) induced arthritis. We applied micro-computed tomography (μCT) during three arthritis experiments and one control experiment to image the metatarsals of the hind paws and to investigate the effect of experimental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…We took advantage of the variable response to MTX to grade the prevention of functional deficits according to the clinical score. Like in previous imaging studies [12, 13], we showed that ankle bone degradation was increased in arthritic mice. Moreover, MTX poor responders exhibited the same bone degradation as untreated CIA mice, and significantly higher erosion compared with controls and also mild and MTX high responders.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We took advantage of the variable response to MTX to grade the prevention of functional deficits according to the clinical score. Like in previous imaging studies [12, 13], we showed that ankle bone degradation was increased in arthritic mice. Moreover, MTX poor responders exhibited the same bone degradation as untreated CIA mice, and significantly higher erosion compared with controls and also mild and MTX high responders.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, the relationship between clinical score and functional deficits has been scarcely studied. Although recent advances in image acquisition and analysis offer a large panel of non-invasive and automated techniques to characterize functional capacities in animals, these approaches have been rarely used to detect pain [5, 6], locomotion deficits [712], and bone erosion [12, 13] in different rodent models of arthritis. Moreover, no systematic and longitudinal study has been performed so far to precisely quantify sensory and motor deficits in mouse models of arthritis (under treatment or not) and to correlate them with the clinical score (i.e., the gold standard evaluation of arthritis severity).…”
Section: Introductionmentioning
confidence: 99%